(untitled) (European Journal of Marketing and Economics, 2018)
The main purpose of this paper is to investigate the relationship between unemployment and GDP growth in 7 countries of Western Balkan, precisely it studies the relationship of GDP-growth as a dependent variable with unemployment, foreign direct investment, and remittances as independent variables. The high unemployment rate in the Western Balkans is one of the main challenges those countries face, whereas unemployment together with GDP-growth represents the fundamental indicators of the level of capacity utilization and economic development. Those problems reflect economic stagnation and the inability to utilize available production capacities, causing a decline in the standard of living for the population. The paper studies the unemployment problem during 2001-2015 as a base study and the labor market of the Western Balkans, as a comparative model between these countries. The data have been processed in the STATA 12 program and these tests were applied: Effective Effect Model, Random Effects Pattern, Hausman Taylor Recording. The study also comprises secondary data gathered from official institutions of local and international statistics. Based on the empirical results is it found out that there exists a trade-off between unemployment and economic growth in Western Balkan countries, meanwhile, the model suggests that an increase by one percent point of unemployment will reduce GDP-growth by 0.5 percent points.